Knowledge Sharing as Media of Proactive Personality to Influence Teachers' Innovative Work Behavior - Riani Tustia Dewi; Eka Suhardi; Soewarto Hardhienata (Journal of Innovation in Educational and Cultural Research, 2023)
Teachers must implement and improve innovative work behavior to maintain educational professional development and school organization. This study aims to analyze the influence of a proactive personality on teachers' innovative work behavior by considering the mediating role of knowledge sharing. The method used in this research was a quantitative survey. Data were collected through questionnaires distributed to 194 private elementary school teachers and analyzed using a Partial Least Square (PLS) approach, a Structural Equation Modelling (SEM) technique. The result shows that proactive personality and knowledge sharing significantly influence innovative work behavior. A proactive personality also has a significant influence on knowledge sharing. And the important finding of this research is knowledge sharing as a mediator of proactive personality to innovative work behavior. Thus, the study's findings can be used to develop a strategy to increase teachers' innovative behavior in schools by creating teacher knowledge-sharing activities and enhancing their proactive personality traits.